Gooseberry Park - Rylant, Cynthia; Howard, Arthur (San Diego : Harcourt Brace, 1995)
When a storm separates Stumpy the squirrel from her newborn babies, her animal friends come to the rescue.
G5
Keywords: Squirrels -- Fiction; Animals -- Fiction